Proceedings of the 8th European Conference on Interactive TV and Video 2010
DOI: 10.1145/1809777.1809820
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the usage of payment services through digital television in Italy

Abstract: This is an exploratory study about factors affecting the usage of Tgovernment services for payments through Digital Terrestrial Television (DTT). The widely known predicting model of ICT user acceptance UTAUT (Unified Theory of acceptance and Use of Technology) was applied to recognize those factors affecting usage, exploiting a pre-existing dataset coming from the Italian Tgovernment project named "Services for citizens via DTT". The key moderators of the model (i.e. age, gender, experience, voluntariness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Confidentiality is determined by protecting information, such as user identity, credit card information, and banking information, when purchasing products and services online [65]. This functionality means that the data must be secure between the parties detailed in the online payment.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…Confidentiality is determined by protecting information, such as user identity, credit card information, and banking information, when purchasing products and services online [65]. This functionality means that the data must be secure between the parties detailed in the online payment.…”
Section: Hypothesis 3 (H3)mentioning
confidence: 99%
“…Furthermore, in the particular case of e-health, it is necessary to consider an additional construct [13] concerning security perception, privacy protection, and personal data confidentiality.…”
Section: Facilitating Conditions (Provided User Support)mentioning
confidence: 99%
“…The literature suggests that the PAYG concept has not been yet investigated within the TV domain with a limited number of studies looking into the issue of payment services through iTV. One of these studies held in Italy [53] has found that that the concept of bill payment through iTV is appreciated by users, but the actual procedure for service use can be still cumbersome, in comparison to the other channels used for payments such as the post office or the Internet.…”
Section: Pay-as-you-go and Televisionmentioning
confidence: 99%